Interaction between Cu(II) and the Nucleobases in Solution - Cheng, Howard; Huq, Fazlul; Farhad, Mohammad (Asian Journal of Chemistry, 2016)
The interaction between Cu2+ and nucleobases viz. adenine and guanine, has been followed by UV-difference spectrophotometry, high pressure liquid chromatography and molecular modeling. Cu2+ is found to form 1 : 1, 1 : 2 and 1 : 3 adducts with adenine and 2 : 1 and 1 : 1 adducts with guanine. In the adducts, the metal ion is believed in a distorted octahedral geometry being coordinated to adenine or guanine ligands and a number of water molecules. In all of the adducts except the 1 : 1 adduct between Cu2+ and guanine, there are one or more intramolecular H-bonds resulting into the formation of macrochelates.